О первоначальной территории расселения антов и их продвижении к Балканскому полуострову - Любичев, М.В. (My University, 1995)
Lyubichev M. V. About Primary Territory of Ants's Settling and Their Movement to the Balkans The ants are identified with the Penkov's culture in the present time. The Penkov's relics of the past have spreading in the forest-steppe zone from Prut to Seversky Donets. Dnieper-Donetz's region is an important part of the Pencov's area. Here it culture was formed ov the base of Post-Zarubinetz's and Kiev's monuments. In the early period its culture is characterized by Kiev's relics of the past in housebuilding and cheramics. But in the beginning of the Middle Ages / end. 5-beg. 6 cent. A. C./ the ants crossed Dnieper and advanced to the Prut and Danube.